The winter is coming: seasonal variations in BDNF levels among older adults in a high-latitude region - a preliminary study - Castillo-Aguilar, Matias; Mabe-Castro, Diego; Mabe-Castro, Matias; Mendes, Thiago Teixeira; Concha-Cisternas, Yeny; Guzman-Munoz, Eduardo; Nuñez-Espinosa, Cristian (My University, 2025)
Objective To evaluate seasonal changes in plasma Brain-Derived Neurotrophic Factor (BDNF) from the start to the end of winter and identify moderating factors.Methods An observational longitudinal study of 17 community-dwelling older adults (mean age 76.4 +/- 5.6 years; 12 women) was conducted with assesments performed at the beginning and at the end of the winter, which included multi-frequency bioelectrical impedance analysis for body composition, standardized physical performance testing, cognitive and anxiety screening, and plasma BDNF quantification by enzyme-linked immunosorbent assay. Data were analyzed using hierarchical Bayesian mixed-effects models with time-by-covariate interaction terms; inference was based on posterior medians and 95% highest-density credible intervals.Results Plasma BDNF decreased from the first to the second assessment. This association remained after adjustment for baseline cognitive performance and anxiety. Physical performance was not associated with attenuation of the seasonal decline.Conclusions In this small longitudinal cohort, winter was associated with a reduction in plasma BDNF in older adults, independent of baseline cognition and anxiety. These results require replication in larger samples.
Keywords: brain-derived neurotrophic factor; seasonal variation; winter; older adults; cognition; anxiety